Diketopyrrolopyrrole-based novel ratiometric fluorescent chemodosimeter for Hg2+ detection in aqueous solution and in living cells. (November 2016) - Bi, Shiming; Zhang, Guanjun; Wu, Yue; Wu, Shengying; Wang, Limin
Abstract: A new ratiometric fluorescent chemodosimeter based on the skeleton of diketopyrrolopyrrole was rationally designed and synthesized, which presented high sensitivity, selectivity for Hg 2+ over other metal ions in aqueous solution leading to further applications of cell imaging. Red shift of chemodosimeter on absorption and fluorescence spectra upon Hg 2+ binding was observed, which changed linearly with increase of Hg 2+ . This phenomenon was a typical deprotection process of acetal groups which increased the conjunction of DPP core that were confirmed by DFT. Graphical abstract: Highlights: A new Diketopyrrolopyrrole-based ratiometric probe were designed and synthesized. The recognition mechanism had been fully proved (deprotection of acetal groups). It presented high sensitivity, selectivity for Hg 2+ over other metal ions. It works perfectly in aqueous solution. It has further applications of Hg 2+ detection in living cells.